A Comparison of Homogenization vs. Enzymatic Lysis for Microbiome Profiling in Clinical Endoscopic Biopsy Tissue Samples - Zhang, Chao; Thakkar, Prashant V.; Powell, Sarah Ellen; Sharma, Prateek; Vennelaganti, Sreekar; Betel, Doron; Shah, Manish A. (Frontiers in Microbiology, 2019)
Identification of the human microbiome has proven to be of utmost importance with the emerging role of bacteria in various physiological and pathological processes. High throughput sequencing strategies have evolved to assess the composition of the microbiome. To identify possible bias that may exist in the processing of tissue for whole genome sequencing (WGS), it is important to evaluate the extraction method on the overall microbial content and composition. Here we compare two different methods of extraction, homogenization versus enzymatic lysis, on gastric, esophageal and colorectal biopsies and survey the microbial content and composition using WGS and quantitative PCR (qPCR). We examined total bacterial content using universal 16S rDNA qPCR as well as the abundance of three phyla (Actinobacter, Firmicutes, Bacteriodetes) and one genus (Fusobacterium). We found minimal differences between the two extraction methods in the overall community structure or in the abundance of specific clade. Furthermore, based on our qPCR analysis, neither method demonstrated preferential extraction of any particular clade of bacteria, nor significantly altered the detection of gram-positive or gram-negative organisms. However, although the overall microbial composition remained the same and the most prevalent bacteria could be detected effectively using either method, we demonstrate that the homogenization extraction method provides higher microbial DNA content and higher read counts from human tissue biopsy samples of the gastrointestinal tract.